Synthesis of Curcumin-Loaded Complex Coacervate of Chitosan Phosphate and Sodium Alginate and Study of their Antibacterial Activity - Sarma, Arunima; Deka, Chayanika; Devi, Sashi Prava; Kakati, Dilip Kumar (Indian Journal of Pharmaceutical Education and Research, 2024)
Background In a system of two oppositely charged colloids a spontaneous liquid-liquid phase separation is termed as complex coacervation and the separated phase is called coacervate. In recent times coacervates prepared from different colloidal systems have found extensive uses in the microencapsulation of bioactive molecules including drugs. The search for new coacervation systems and coacervates with novel properties remains an active area of research. In the present work preparation of complex coacervate from chitosan phosphate and sodium alginate for subsequent use for encapsulation of curcumin is reported. Materials and Methods Chitosan was first modified to chitosan phosphate. It was then reacted with sodium alginate to form the complex coacervate. Several parameters like ratio of concentration of the chitosan phosphate to alginate, pH of the reaction media were varied to attain the optimum condition for the maximum yield of the coacervate. Results It was found that the maximum amount of coacervate formed at pH 3.6 and at the ratio of 5:4 by volume of the 3% solution of alginate and chitosan phosphate. The maximum loading efficiency of curcumin was found to be 84%. Swelling and release studies were carried out at different pH and the maximum swelling and percentage of release was observed at pH 9. The curcumin loaded coacervate showed mild antibacterial activity against Staphylococcus aureus, Bacillus subtilis and Enterobacter aerogenes. Conclusion Results from Fourier transform infrared spectroscopy, thermogravimetric analysis, powder x-ray diffraction and scanning electron microscopy supported successful encapsulation of curcumin in the chitosan phosphate/alginate coacervate. Swelling and release studies could be modulated by changing the pH of the medium. A sustained release behavior of curcumin over a period of 72 hr was observed without the loss of physical integrity of the coacervate.
Keywords: Curcumin; Chitosan Phosphate; Sodium Alginate; Staphylococcus aureus; Bacillus subtilis; Klebsiella pneumonia; Enterobacter aerogenes